EVALUATION OF OFFICE CHAIR DESIGN FROM ERGONOMIC AND ANTHROPOMETRIC PERSPECTIVES - Fitrianto, Taufik Ramadhan; Rahmat, Bahtiar; Nugroho, Alfani Risman; Prakoso, Galih; Afifah, Anshah Silmi; Anggiriani, Siska; Juwitasari, Dhian (J@ti Undip: Jurnal Teknik Industri, 2025)
Workplace seating that does not match user anthropometry often leads to discomfort and musculoskeletal disorders (MSDs). This study evaluates the office chairs used at the Politeknik Industri Furnitur dan Pengolahan Kayu Kendal by combining discomfort analysis and anthropometric mismatch assessment. Thirty-two employees (16 males, 16 females) participated, completing the Nordic Body Map (NBM) questionnaire and providing seated anthropometric measurements. The NBM results revealed that lower back discomfort was the most common complaint, particularly among female respondents, who also reported higher discomfort in the neck, shoulders, and upper back. Mismatch analysis confirmed severe incompatibilities between existing chair dimensions and user anthropometry, with seat height (100% mismatch for both genders) and seat depth (94% for men, 88% for women) as the most problematic. Based on these findings, a redesigned chair was developed, lowering seat height by 30 mm and reducing seat depth by 66 mm, alongside adjustments to backrest and armrest dimensions. Comparison with Indonesian (SNI) and international ergonomic standards (ISO 9241-5, BIFMA G1, EN 1335-1) showed that the redesign falls within recommended ranges. The study demonstrates how anthropometry-based redesign can reduce mismatch and improve comfort, providing practical guidance for the local furniture industry.